Distribution of Addressee’s Attention in News Headlines - Talavira, Nataliia (Studia Philologica, 2026)
The goal of the paper is to examine how readers’ attention is split across different structural positions in English news headlines, drawing on denoted relations established by various morphosyntactic constructions. The latter are defined as form-meaning pairings entrenched in long-term memory in a ready-made form, requiring less cognitive effort when speakers choose a necessary linguistic unit. Three headline constituents encompass the attractor, catching the recipient’s eye; the keeper, retaining their attention; and the nudger, stimulating them to turn to the text body. The attention-distributing structure of news headlines is filled in with various communicative constructs as speech manifestations of mentally fixed morphosyntactic constructions: agentive, predicate, locative, causal, content- and recipient-naming, purpose-related, temporal. Agentive constructs, used in the attention-grabbing position of the headline, have a high persuasive status as they denote entities close to the target audience. The most convincing are constructs with one or two slots filled, as they name famous personalities, while the status of ordinary people is increased by a toponym, a component designating an unusual characteristic, and numerals indicating a large number of event participants. The keeper is filled in with the predicate pairings, which denote acts of speaking, damage infliction, social coercion, motion, transfer, aspects of the action, emotions of the participants, and entity existence. The nudger can contain various types of communicative constructs with causal being the predominant ones; locative pairings indicating a place in the proximity or vital for the readers; recipient-naming units, denoting the person getting some benefit or obtaining some object; content-naming constructs, representing the information expressed by the event participant; purpose-related pairings, reflecting an exceptional aim of the happening; and the least numerous temporal units, giving the approximate time of the event or indicating an unexpected duration of the occurrence.